1999
DOI: 10.1161/01.res.85.12.1173
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vascular Graft Grown Within Recipient’s Own Peritoneal Cavity

Abstract: —A method by which to overcome the clinical symptoms of atherosclerosis is the insertion of a graft to bypass an artery blocked or impeded by plaque. However, there may be insufficient autologous mammary artery for multiple or repeat bypass, saphenous vein may have varicose degenerative alterations that can lead to aneurysm in high-pressure sites, and small-caliber synthetic grafts are prone to thrombus induction and occlusion. Therefore, the aim of the present study was to develop an artificial blood conduit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
220
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(235 citation statements)
references
References 12 publications
12
220
1
2
Order By: Relevance
“…By day 7 a distinct capsule of round cells and extracellular matrix (ECM) had formed, and by day 14 cells had elongated and organised into multilayered strata within a fibrillar matrix. Ultrastructurally, these elongated cells had the characteristics of myofibroblasts and contained large amounts of rough endoplasmic reticulum and bundles of peripherally distributed myofilaments (Campbell & Ryan, 1983;Campbell et al, 1999). A layer of mesothelial cells was also observed to cover the developing capsule.…”
Section: Application Of the Foreign Body Response To Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…By day 7 a distinct capsule of round cells and extracellular matrix (ECM) had formed, and by day 14 cells had elongated and organised into multilayered strata within a fibrillar matrix. Ultrastructurally, these elongated cells had the characteristics of myofibroblasts and contained large amounts of rough endoplasmic reticulum and bundles of peripherally distributed myofilaments (Campbell & Ryan, 1983;Campbell et al, 1999). A layer of mesothelial cells was also observed to cover the developing capsule.…”
Section: Application Of the Foreign Body Response To Tissue Engineeringmentioning
confidence: 99%
“…However despite intensive testing, the lack of compliance/strength of the resulting tissue, as well as the absence of an endothelial lining, resulted in unacceptably high rates of thrombosis, dilatation and aneurysm (Conte, 1998). More recently, our laboratory and others have used the peritoneal cavity as a 'bioreactor' to produce autologous tissue for replacement/repair of arteries (Campbell et al, 1999Chue et al, 2004) and other hollow smooth muscle organs, specifically bladder, uterus, vas deferens and urethra (Gu et al, 2009). De Visscher and co-workers used a similar technique to pre-seed acellular matrix scaffolds from bovine pericardium for use as tissue engineered heart valves (De Visscher et al, 2007, 2008Vranken et al, 2008) while Hayashida et al (2007) reported satisfactory function and mechanical properties for 'biovalves' prepared by embedding synthetic scaffolds subcutaneously for 4 weeks.…”
Section: Application Of the Foreign Body Response To Tissue Engineeringmentioning
confidence: 99%
“…However, this will require an understanding of phenotypic differences between vascular and such nonvascular SMC types and an investigation into the possibility of retraining these differentiated cell types to assume a phenotype more typical of VSMCs, while retaining their own inherent high elastogenic capacity. Recently, Campbell et al [117][118][119] reported on recruitment of macrophage-like cells from peritoneal fluid onto silastic tubes implanted within peritoneal cavities of rats and their production of a fibrous tissue capsule. Although the everted tubular tissue capsule exhibited distinct circumferential layers resembling the vascular tunics (i.e., a luminal mesothelium, an outer collagenous layer, and a layer of myofibroblasts in the middle), little elastin was observed in these constructs.…”
Section: Cell-based Approaches To Elastic Matrix Engineeringmentioning
confidence: 99%
“…3 Seven day calluses were used for force measurement as such calluses are fibrous in nature and ideal for measurement of active force production. 3 [21][22][23][24] KH solution had the following composition (mM): NaCl 135; KCl 5; MgCl 2 3; NaH 2 PO 4 0.8; HEPES 10; calcium (Ca 2þ ) 1.2; glucose 5. Solution temperature was 228C and its stable pH was stable at 7.4 for a period of at least 6 h.…”
Section: Animals and Rib Fracture Surgerymentioning
confidence: 99%